2018
DOI: 10.3390/children5110146
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Modifiable Risk Factors in Pediatric Onset Multiple Sclerosis: Building for the Future

Abstract: Knowledge of the effect of modifiable lifestyle factors in the pediatric multiple sclerosis (MS) population is limited. We therefore conducted a scoping review, following the framework provided by Arksey and O’Malley. Four databases were searched for pediatric MS and modifiable lifestyle factors using index terms and keywords, from inception to May 2018. All quantitative and qualitative primary articles were included and limited to English and full text. Of the 7202 articles identified and screened, 25 full-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Intriguingly, children with POMS performed better than matched controls in managing sleep hygiene, and higher levels of physical activity were associated with fewer sleep/rest fatigue symptoms [ 195 ]. It is noteworthy that, quite similar conclusions were also reached by other independent authors [ 183 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Intriguingly, children with POMS performed better than matched controls in managing sleep hygiene, and higher levels of physical activity were associated with fewer sleep/rest fatigue symptoms [ 195 ]. It is noteworthy that, quite similar conclusions were also reached by other independent authors [ 183 ].…”
Section: Discussionsupporting
confidence: 91%
“…Due to its effects on levels of disease activity, depression and fatigue, and lower moderate to vigorous physical activity, prevention and/or treatment of obesity/being overweight has been deemed a critical aspect of POMS as well [ 183 ]. A case-control study comparing the BMI data of 60 French youths with POMS showed that overweight and obesity are more frequently observed at diagnosis, particularly in boys with POMS compared with non-neurologic controls and healthy French children.…”
Section: Diet and Nutrition Related Issues In Pediatric-onset Msmentioning
confidence: 99%
“…Moreover, to add towards the burden of MS, a lack of awareness among teachers was reported in some of the studies reviewed [18,29,33,39]. Here, one study reported that teachers commonly misinterpreted fatigue-related symptoms of children as "laziness" [18,59]. As a consequence, increased pressure of school-related work and poorer academic performance could predispose CAMS towards poorer mental health and possibly negatively influence employment-related outcomes later on [40].…”
Section: Physical and Psychological Impact Of Msmentioning
confidence: 99%
“…SES can impact health directly due to poor accessibility to health care, limited knowledge about and adherence to treatment, and variable nutrition. Genetic risk factors and interactions between several risk factors (second-hand smoke, genetic predisposition, physical functioning) were also evaluated [119,120,121]. A recent pilot study [26] searched for genetic signatures associated with cognitive impairment in patients with POMS.…”
Section: Other Risk Factors Of Cognitive Impairmentmentioning
confidence: 99%